Urban cemetery animals: an exploration of animals' place in the human cemetery*. (2nd January 2018) - Petersson, Anna; Cerwén, Gunnar; Liljas, Maria; Wingren, Carola
Abstract: This paper investigates the place of animals in the contemporary Swedish human cemetery. It does this by looking at how animals are admitted to cemeteries – alive and dead, above and below ground, physically as well as symbolically. The aim is to shed light on the various ways that animals are experienced and treated in the cemetery, and to explore how this both reflects our changing attitudes to animals and our changing attitudes to death. The paper draws on the findings from a qualitative interview study carried out at the Eastern Cemetery in Malmö, Sweden, and a follow-up study of a turtle pond, in Malmö-Limhamn Cemetery. Two different perspectives relating to animals in the cemetery were common to these studies: (1) the liminal role of the companion animal; and (2) aesthetics and care in relation to wild and domesticated animals. The two perspectives, considered as findings in their own right, are used in this paper as a foundation for discussing questions relating to how urban cemetery animals can enrich the cemetery environment and increase the importance of urban cemeteries today and in the future.